Fungsi Dinas Tenaga Kerja dan Transmigrasi dalam Menanggulangi Masalah Ketenagakerjaan di Kota Kupang - Muhamad Farid Ridha; Saryono Yohanes; Yohanes G. Tuba Helan (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The purpose of this research is to analyze the function of the Kupang City Manpower and Transmigration Office in tackling employment problems and efforts to overcome the obstacles faced in the city of Kupang. This type of research uses Sociological juridical research. The research location was carried out at the Kupang City Manpower and Transmigration Office. The types of data used in this research are primary data and secondary data. Data collection techniques with observation, interviews, and documentation. Data processing techniques with editing, data classification, data systematization, data reduction, and data verification. Data analysis techniques are analyzed using qualitative descriptive juridical methods. The result of this research is that the Kupang City Manpower and Transmigration Office (Disnakertrans) has a strategic function in managing and overcoming labor problems in the region. Disnakertrans is responsible for implementing labor policies that include job placement, transmigration, employment expansion, and problem solving in industrial relations. The main functions of the Disnakertrans include guidance, supervision, control, public services, program development, budget supervision, as well as policy development and dispute resolution. There are 2 factors that inhibit the Disnakertrans in tackling labor issues in Kupang City, namely the budget and human resources. Efforts need to continue to be made to provide training, direction, and guidance to human resources so that they can work more professionally, purposefully, and responsibly in accordance with their duties.